Risk Factors Of Anemia In Pregnant Women - Oktarinda Napitupulu; Yulianto Yulianto; Suprida Suprida (Poltekkes Kemenkes Palembang, 2023)
Anemia in pregnant women is categorized as a global health problem with a prevalence reaching 36.5%. In Indonesia, the incidence of anemia in pregnant women reaches 48.9%. The highest prevalence of pregnant women with anemia at the Puskesmas level in Palembang City was at the Merdeka Health Center, which was 12.47%. Research Objectives: To determine the relationship between maternal age, gestational age, parity, KEK status, gestational age, and the incidence of anemia in pregnant women. Research Method: Observational study with case-control research design. This research was conducted at the Merdeka Palembang Health Center from April 1 2023 to May 25, 2023. The sample in this study totaled 104 respondents consisting of 52 case respondents and 52 control respondents using register book data. The results of the study: there is a relationship between gestational age (p-value = 0.013 OR value = 3.195), KEK status (p-value = 0.013 OR value = 3.701), pregnancy interval (p-value = 0.044 OR value = 4.382) and the incidence of anemia in pregnant women and there is no relationship between maternal age (p-value = 1,000 OR = 1,000) and parity (p-value = 0.759 OR = 1.462) with the incidence of anemia in pregnant women. Gestational age, KEK status, and gestational spacing have a greater possibility of anemia when compared to maternal age and parity.